Bibliometric Analysis of Public Leadership: Global Research Keyword Mapping (2019-2024) - Rahman, Nawir (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to analyze current public leadership trends using a bibliometric approach. This research is relevant given the importance of public leadership to achieve organizational goals through strategic planning, resource management, and its influence on subordinates. The main objective of the study is to identify keywords that frequently appear in the related literature, mapping relevant topics, around the world in the 2019–2024-time frame. The method used is to collect data through the Publish or Perish application from two main databases, namely Scopus and Google Scholar, then analyze it using Mendeley to identify author keywords. Further bibliometric analysis was carried out using VOSviewer to map the relationships between keywords and distribute the research geographically. The results showed that the keyword "organizational behavior" was the most dominant theme in the study, with a strong relationship with various other topics. These keywords are at the center of the network, reflecting the importance of organizational behavior in the context of leadership. In addition, keywords such as "public service delivery", "healthcare leadership", "public health leadership", and "ethical leadership" also show significant relevance, describing leadership dimensions that include the public sector, health, and ethics. Various themes such as "diversity and inclusion", "job satisfaction", "educational leadership", and "collaborative governance" also enriched the scope of the research, showing the relationship between leadership and aspects of culture, education, job satisfaction, and collaborative governance. The contribution of this study lies in presenting a comprehensive overview of research trends on public leadership that can provide new insights for researchers and implementers of public organizations